Peran Media Sosial dalam Mempengaruhi Kesadaran Konsumtif Generasi Z melalui Tren Thrifting sebagai Gaya Hidup Berkelanjutan. - Syafitri, Chantika Zabrina Lailatul (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2025)
This study investigates the role of development communication via social media in shaping Generation Z's consumer awareness towards thrifting as a sustainable lifestyle. Facing rising consumerism and environmental concerns, Gen Z, as digital natives, increasingly embraces thrifting. Using a Systematic Literature Review (SLR) following the PRISMA framework.Findings reveal social media's crucial role in fostering Social Environmental Awareness, driving Gen Z's thrifting intent. The Need for Uniqueness and Brand Awareness also significantly influence this trend. Importantly, past preconceptions and social prestige no longer deter thrifting, signifying a positive shift amplified by social media. Social media platforms lsuch as TikTok and Instagram facilitate community building and advocacy, with Gen Z actively contributing to the trend's growth. In essence, social media acts as a transformative force, guiding Gen Z towards more conscious and sustainable consumption through thrifting.Keywords: Social Media, Generation Z, Thrifting, Sustainable Lifestyle, Consumer Awareness.